Discrimination Based on Sexual Orientation and Social Security Rights in the Case Law of the IACtHR and the ECtHR. A Tale of Divergences? - Clérico, Laura (Revista de la Facultad de Derecho, 2019)
For some years now, universal and regional human rights protection systems converge in the extension of the grounds for prohibiting discrimination, as in the case of sexual orientation. However, a micro-study of the similarities and divergences in the equality test for differentiated treatment by social orientation in the access to social security rights, demonstrate the divergences between the Inter-American Court and the ECtHR. Thus, this paper argues that the ECHR assumes a conditioned incrementalit approach regarding the recognition of LGBTI rights against the categorical approach of the Inter-American Court as a speed adopter. The lack of a factual European consensus on the claim and the granting of a wide margin of state appreciation gain primacy in the face of the equality test in the ECtHR. On the contrary, the IACtHR applies an examination of intensive equality if the differential treatment is based on the sexual orientation of the persons although there is no Inter-American consensus on the subject. The article concludes thus differentiating two types of human rights adjudication approach.
CRIS-Team WoS Importer:2019-09-13